Aptamer-coated track-etched membranes with a nanostructured silver layer for single virus detection in biological fluids - Kukushkin, Vladimir; Kristavchuk, Olga; Andreev, Evgeny; Meshcheryakova, Nadezda; Zaborova, Olga; Gambaryan, Alexandra; Nechaev, Alexander; Zavyalova, Elena (Frontiers in Bioengineering and Biotechnology, 2023)
Aptasensors based on surface-enhanced Raman spectroscopy (SERS) are of high interest due to the superior specificity and low limit of detection. It is possible to produce stable and cheap SERS-active substrates and portable equipment meeting the requirements of point-of-care devices. Here we combine the membrane filtration and SERS-active substrate in the one pot. This approach allows efficient adsorption of the viruses from the solution onto aptamer-covered silver nanoparticles. Specific determination of the viruses was provided by the aptamer to influenza A virus labeled with the Raman-active label. The SERS-signal from the label was decreased with a descending concentration of the target virus. Even several virus particles in the sample provided an increase in SERS-spectra intensity, requiring only a few minutes for the interaction between the aptamer and the virus. The limit of detection of the aptasensor was as low as 10 viral particles per mL (VP/mL) of influenza A virus or 2 VP/mL per probe. This value overcomes the limit of detection of PCR techniques (∼103 VP/mL). The proposed biosensor is very convenient for point-of-care applications.